2013
DOI: 10.1007/s00167-013-2551-7
|View full text |Cite
|
Sign up to set email alerts
|

Tendon quality in small unilateral supraspinatus tendon tears. Real-time sonoelastography correlates with clinical findings

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
1
27
1
1
Order By: Relevance
“…Tudisco et al use adjacent bone and Busilacchi et al used fat pad as the reference tissue to calculate strain ratio [26,27]. Fat pads were established as having a mosaic pattern with different colors, as described by Drakonaki et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…Tudisco et al use adjacent bone and Busilacchi et al used fat pad as the reference tissue to calculate strain ratio [26,27]. Fat pads were established as having a mosaic pattern with different colors, as described by Drakonaki et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not possible to measure these changes with the help of routine diagnostic imaging studies like B-mode ultrasonography and magnetic resonance imaging (MRI). 3 Real-time sonoelastography (RTSE) is a noninvasive, relatively new ultrasound-based imaging method that provides information on the mechanical properties of tissues (stiffness and elasticity), reflecting their quality. 4 It is based on the principle that tissues deform and move away from the ultrasound transducer when pressure is applied.…”
mentioning
confidence: 99%
“…3,5,6 A recent study of De Zordo et al 7 showed that injured tendons exhibited a softer tissue color on RTSE when compared to healthy tendons in the evaluation of Achilles tendinopathy. Tudisco et al 3 reported that RTSE was a feasible method applicable in small supraspinatus tears, and there was a correlation between RTSE findings and clinical results of the patients. Supraspinatus tendon elasticity is a challenging topic for research because of the high susceptibility of the tendon for injury.…”
mentioning
confidence: 99%
“…[3][4][5]. A negative correlation between strain index and pain, and a strong positive correlation with functional scores 59 was also reported. SE showed a good to very good intra and inter user and day by day repeatability 61 that could be very useful in the preoperative assessment of tendon quality 60 .…”
Section: Shouldermentioning
confidence: 99%
“…In case of small supraspinatus tears, several Authors 53,59,60 reported the torn tendons to be softer (mean strain index 0.75 ± 0.08) compared with the contralateral healthy shoulder (1.01 ± 0.07) (Figs. [3][4][5].…”
Section: Shouldermentioning
confidence: 99%